The theory of harm under the Malaysian Competition Act 2010 - Abdul Rahman, Nasarudin; Ahamat, Haniff; Abd Ghadas, Zuhairah Ariff (2015)
The Malaysian Competition Act 2010 (the CA 2010) seeks to promote the process of competition in the market by preventing anti-competitive conduct that harms to competition. However, what harms to competition is not clearly spelt out in the Act neither in its subsequent guidelines. Without a proper application of the theory of harm, the competition authority will not be able to provide a consistent approach to the assessment of the competition issues especially in determining whether or not a conduct is anti-competitive. This paper aims to analyze how and to what extent the Malaysian Competition Commission (MyCC) applies the theory of harm in the competition law analysis. The paper will first analyze the theory of harm that embodied in the competition law provisions and its guidelines and will then support the analysis with two recent cases which had been decided/proposed by the Malaysian Competition Commission (MyCC). This paper argues that there is no standard application of the theory of harm in the context of the Malaysian competition law. Harms to competition may be interpreted as harms to consumers. It may also be narrowly interpreted as harms to market mechanism and opportunity to compete, through for example unjustified exclusion of rivals from the market without an explicit proof that those conduct reduce the aggregate consumer welfare. In most situations, the issue of competitive harm is not about the interpretation but rather the issue of proof that a particular conduct really harms competition and consumers.